Firm Culture and Innovativeness Among Logistics Companies in Malaysia - Awanis Ku Ishak; Azahari Ramli; Zulkifli Aziz; Ahmed Mohammed Kamarudden; Khairunnisa Ahmad Shakir (International Journal of Supply Chain Management, 2019)
The logistics industry environment is continuously changes with intense competition and demanding customers. Hence, appropriate firm culture that initiates firm innovativeness is required. At present, innovativeness research on logistics companies is still limited. Yet, empirical research showed firm innovativeness provide companies capabilities to achieve lower cost while rendering higher quality services that meet all requirements of potential customers, introduce new products, services, business, environmental issues and maximum utilization of information technology. Although there is general impression on low level of innovativeness in SMEs around the world, this research aims to demonstrate that there is potential higher degree of innovativeness within Malaysia’s logistics sector. Hence, this study objective is to gauge firm culture relationship with firm innovativeness. The study used simple random sampling technique where 226 companies were selected from total population of 500 logistic companies registered under Federation of Malaysian Freight Forwarders via survey. Findings revealed firm innovativeness among logistic companies is at high level and firm culture has a significant positive correlation with firm innovativeness. In fact, firm culture specifically adhocracy and market orientation culture significantly and positively influence on logistic firm innovativeness in Malaysia. This study brings new insight on innovativeness among Malaysian logistic companies.